Self-assembling of surface active drug amitriptyline hydrochloride in association with additives: Role of surface activity in the pharmaceutical applications - GÖKTÜRK, SİNEM (My University, 2022)
The self-assembling of surface active antidepressant drug amitriptyline hydrochloride (AMT) has been studied to determine the micellar solution behavior in the presence of polar (methanol and ethanol), dipolar aprotic solvents (acetone and 1,4 dioxane), salt (NaCl) and water structure-breakers (urea) at 298 K using surface tension and electrical conductivity measurements. The counterion binding parameter and the ionization degree of AMT micelles have been determined by electrical conductivity measurements. To better analyze the influences of additives on micellar behavior of AMT, surface features of AMT were defined using Gibbs Adsorption Isotherm in water and in association with various amounts of additives conducted by surface tension measurements. Both conductometric and surface tension experiments were also used to detect the critical micelle concentration (CMC) of AMT. The experimental results indicated that CMCs of AMT were influenced in the presence of additives. Selfaggregation of AMT was totally inhibited when methanol, ethanol, acetone, 1,4 dioxane, and urea concentration is attained to a certain value while the CMC of AMT reduced with the increase in concentration of NaCl.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Amitriptyline hydrochloride; amphiphilic drugs; conductivity; critical micelle concentration; surface active drugs; surface tension